Post-COVID-19 Unemployment Dynamics: Trends, Causes, and Implications for Economic Recovery - Afdhol Rinaldi; Febyyanti; Naufal Wahyu Harahap; Jihan Absharina Gusliwan; M. Hilmy Faizhan (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
Unemployment remains one of the critical challenges in the post–Covid-19 period, as many countries—including Indonesia—struggle to restore labor market stability. The pandemic triggered large-scale disruptions in economic activity, leading to job losses across multiple sectors. This study aims to analyze the dynamics of unemployment after Covid-19 by examining its trends, underlying causes, and implications for economic recovery. Using a descriptive qualitative approach supported by secondary data from national and international labor reports, this study identifies shifting unemployment patterns influenced by structural changes in the labor market, digital transformation, and sectoral vulnerabilities. The findings show that post-pandemic unemployment is shaped not only by economic contraction but also by mismatches in labor skills, uneven access to digital opportunities, and the slow recovery of key industries such as tourism and manufacturing. These dynamics have significant implications for economic recovery, particularly in terms of productivity, household income stability, and the effectiveness of government employment programs. The study concludes that comprehensive policy strategies including reskilling initiatives, targeted job creation, and support for digital inclusion are essential to accelerate labor market recovery and sustain long-term economic resilience.